The Effect of Using Wordless Picture Books Strategy on Students’ Ability in Writing Narrative Paragraph - Paidi Gusmuliana; Mardiana Fitri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Many problems in learning English especially writing narrative paragraph are faced by most of the eight grade students of MTs Desa Sawah of Kampar Regency. The students were unable to express ideas in writing narrative paragraph. They were also unable to use good grammatical features, use generic structure clearly, and use vocabulary appropriately. Therefore, the writer was interested in conducting this research. The purpose of this research was to find out students’ ability in writing narrative paragraph taught by using wordless picture books strategy, to find out students’ ability in writing narrative paragraph taught without using wordless picture books strategy, and to find out whether there was any significant difference of students’ ability in writing narrative paragraph taught by using and without using wordless picture books strategy at Islamic Junior High School of Desa Sawah of Kampar Regency. This research is an experimental research, precisely a quasi-experimental research. The total sample of the research was 48 students. The instrument of the research was test. The data were analyzed by using independent sample t-test. It was used to find out whether there is any significant difference of students’ ability in writing narrative paragraph by using and without using Wordless Picture Books strategy to the eight grade students of Islamic Junior High School of Desa Sawah of Kampar Regency. Based on the data analysis by using SPSS 16 version, the writer found that the score of t-test is 9.543 which it is higher than t-table in level significant of 5% (2.02), and in level significant of 1% (2.69). It could be read 2.02<9.543>2.69. It can be stated that Hois rejected and Ha is accepted. It means that there is significant difference of students’ ability in writing narrative paragraph taught by using and without using Wordless Picture Books strategy at the eight grade students of Islamic Junior High School of Desa Sawah of Kampar Regency.